2020
DOI: 10.1111/tid.13433
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolones for BK viral complication after transplantation: Meta‐analysis

Abstract: BK polyomavirus (BKV) infection usually occurs in early childhood and remains quiescent in uroepithelial cells with high prevalence in healthy adults, with up to 90% seropositivity. 1 BKV reactivation occurs in highly immunocompromised patients post transplantation and causes BKV-associated hemorrhagic cystitis (BKV-HC) after hematopoietic stem cell transplantation (HSCT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Fluoroquinolones like ciprofloxacin have been used with some effect. 107 The use of intravenous immunoglobulin is a supportive strategy that can help provide humoral immunity. 108 Leflunomide has been studied but the current data are not very convincing.…”
Section: Bk Virusmentioning
confidence: 99%
“…Fluoroquinolones like ciprofloxacin have been used with some effect. 107 The use of intravenous immunoglobulin is a supportive strategy that can help provide humoral immunity. 108 Leflunomide has been studied but the current data are not very convincing.…”
Section: Bk Virusmentioning
confidence: 99%
“…1 BKV can cause serious complications, such as hemorrhagic cystitis (HC) after hematopoietic stem cell transplantation (HSCT) and BKV-associated nephropathy due to allograft loss after renal transplantation. [1][2][3][4] The frequency of BKV-associated HC (BKV-HC) after HSCT is ∼10%. 1,2 BKV-HC reduces patients' quality of life and may lead to decreased overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…BK polyomavirus (BKV) infects most of the general population during childhood and persists in renal tubular cells and urothelial cells 1 . BKV can cause serious complications, such as hemorrhagic cystitis (HC) after hematopoietic stem cell transplantation (HSCT) and BKV‐associated nephropathy due to allograft loss after renal transplantation 1–4 . The frequency of BKV‐associated HC (BKV‐HC) after HSCT is ∼10% 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a limited number of studies examining its effectiveness in BKVN treatment. A meta-analysis showed that fluoroquinolones did not prevent the development of BKVN after transplantation [21]. Fluoroquinolones may reduce the rate of the BK virus to some extent but may not have sufficient clinical effects [22].…”
Section: Discussionmentioning
confidence: 99%